Adherence to Guidelines in the Treatment of Diabetic Ketoacidosis in Children: An Austrian Survey. Issue 5 (May 2021) - Weinberger, Katharina; Seick Barbarini, Daniela; Simma, Burkhard
Abstract : Background: The aim of this study is to assess the adherence of Austrian physicians to International Society for Pediatric and Adolescent Diabetes guidelines 2009 concerning treatment in diabetic ketoacidosis and whether there is a difference between specialty (endocrinologists or intensivists) or clinical experience. Patients and Methods: An online questionnaire was sent to members of the working groups of the Austrian Society of Pediatric and Adolescent Medicine. Results: Of 106 questionnaires, 56 were included in the analysis. The mean ± SD overall adherence was 60 ± 23.5%. Endocrinologists showed a nonsignificant higher result, related to a significant higher adherence regarding the amount of fluids ( P < 0.05) and tendency to bicarbonate use ( P = 0.052) respectively. No differences were found between participants with different clinical experience. All gave crystalloids, 55% administered initial bolus of 10 to 20 mL/kg per hour, 58% used 1.5 to 2 times fluid maintenance, 87% started insulin after first fluid bolus, 28% gave 0.05 and 0.1 IE/kg per hour to infants and children respectively, and 43% 0.05 IE/kg per hour to all patients. When blood glucose falls, 53% gave glucose and 47% reduced insulin. In cerebral edema, 46% gave at least 2 of 3 recommended measures (fluid reduction, mannitol, or hypertonic saline). In acidosis (pH <6.9), 25% administered bicarbonate (as per guideline) and 52.9% never gave bicarbonate. Conclusions: Adherence to the actual guidelines is 60% and does neither depend on speciality nor on clinical routine. Essential treatment measures (eg, amount of fluids, consequence of rapid glucose fall, bicarbonate use) are not commonly known.